Exploring the use of blended learning to change perceptions towards economics - Aboobaker, Feroza (The IIE, 2015)
The purpose of this exploratory research is to determine the effectiveness of using a blended learning teaching strategy to increase student engagement and changing student sentiment towards the subject of economics. Classroom lessons were extended to an online platform through the use of discussion forums, blogs and online activities. Data was collated using a cross sectional survey design where students were required to provide feedback on the blended learning approach and rank the most enjoyable activities through a questionnaire. The findings revealed that the use of blended learning helped to improve student sentiment towards economics and the relevance of the subject became more apparent. Students preferred activities that included group work and simulation exercises. This would imply that the use of a constructive learning theory in the classroom is an appropriate method to improving student engagement and student attitude towards economics.
Keywords: Blended learning; Economics; Perceptions; Simulation exercises; Constructive learning theory; Group work; Student engagement